2015
DOI: 10.1088/0004-637x/804/2/114
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Estimation for Binary Neutron-Star Coalescences With Realistic Noise During the Advanced Ligo Era

Abstract: Advanced ground-based gravitational-wave (GW) detectors begin operation imminently. Their intended goal is not only to make the first direct detection of GWs, but also to make inferences about the source systems. Binary neutron-star mergers are among the most promising sources. We investigate the performance of the parameter-estimation (PE) pipeline that will be used during the first observing run of the Advanced Laser Interferometer Gravitational-wave Observatory (aLIGO) in 2015: we concentrate on the ability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
177
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(187 citation statements)
references
References 94 publications
8
177
0
Order By: Relevance
“…For a two-detector network, the sky localization forms a characteristic broken annulus [125][126][127][128]. Adding additional detectors to the network would improve localization abilities [129][130][131][132].…”
Section: B Spinsmentioning
confidence: 99%
“…For a two-detector network, the sky localization forms a characteristic broken annulus [125][126][127][128]. Adding additional detectors to the network would improve localization abilities [129][130][131][132].…”
Section: B Spinsmentioning
confidence: 99%
“…See the recent works of Singer et al (2014), Berry et al (2015), Kasliwal & Nissanke (2014) for sky location works using either only two LIGO detectors or the three LIGO-Virgo detectors at staggered (and not full) design sensitivities.…”
Section: Gravitational-wave Detector Networkmentioning
confidence: 99%
“…For our analysis we began generating the waveforms at a lower frequency of 10 Hz in both LIGO and Virgo instruments, allowing us to take full advantage of the low-frequency sensitivity of the instruments, which will be achieved toward the end of the decade. The use of zero-noise mock data sets to estimate parameter measurement accuracy relies on the assumption that the noise is stationary and Gaussian; although Berry et al [38] demonstrated that non-stationary realistic noise does not significantly influence parameter estimation for neutron star binaries, departures from stationarity (noise "glitches") could play a larger role for low-frequency, short-duration IMBHB signals.…”
Section: Simulationsmentioning
confidence: 99%
“…The prior on the single aligned spin χ was fixed to be flat in [−1, 0.6], the range of validity of the SEOBNRv1 [33] approximant. Since this prior distribution does not match the distribution of sources analyzed, we should anticipate that posteriors on individual injections can be centered away from the true values, despite the self-consistency of LALInference, which has been demonstrated to produce X% credible intervals that contain the true value X% of the time [38,39,43]. For example, the low a a priori probability of high-mass extreme-mass ratio injections with non-spinning components, coupled to the asymmetry in the impact of remnant spin on the well-measured central frequency of the dominant ringdown harmonic [e.g., 44], will lead to a typical over-estimate of the inferred total mass for such sources.…”
Section: Simulationsmentioning
confidence: 99%